The Myriad Achievements of Kuningan FM Radio as a Regional Public Broadcasting Institution (LPPL) - Sjuchro, Dian Wardiana; Lusiana, Elnovani; Sjarifah, Nuryah Asri; Sujana, Lusi Romaddyniah (Jurnal Kajian Jurnalisme, 2023)
There is a Local Public Broadcasting Institution (LPPL) that has the support of the regional district head, where the district head has been named the district head who cares about broadcasting, because there are rarely district heads or mayors who care about local public radio in their area. Apart from that, the Head of the Communication and Informatics Service also gave his support and was elected as the head of the service concerned with broadcasting. The public radio is Kuningan FM radio with a frequency of 100.5 MHz, which is located at Jalan Aruji Kartawinata No. 3, Kuningan District, Kuningan Regency, West Java Province. Kuningan FM Radio has the motto “green and culture radio, caring for nature, preserving culture, the excitement that circulates”, with the vision “to actualize the role of local public broadcasting institutions as a unifying media, the leading source of public information towards advanced brass in 2023”. By getting the support and role of the people involved in the organizational structure, it has a positive impact on Kuningan FM radio. The purpose of this study is to describe the ways in which Kuningan FM radio has increased the existence of local public radio among the surrounding community. This study uses a qualitative approach using the case study method. Data collection techniques in this study used observation, interviews, literature and literature review. The results of this study found several factors that made Kuningan FM radio won many awards, namely: the support of the regent, the supervisory board, the board of directors and the role of the people involved in the organizational structure of LPPL Kuningan Regency, innovative programs and events adapted to the needs of the surrounding community, use of streaming channels, as well as consistency in filling out each program.